The evolving gift-giving practices of bicultural consumers. Issue 1 (9th January 2017) - Aung, May; Zhang, Xiying; Teng, Lefa
Abstract : Purpose: The purpose of this study is to offer a better understanding of contemporary consumer behaviour. This study relates to the complex and value-laden phenomenon of "gift-giving" from the perspective of bicultural consumers. The focus was on the gift-giving practices of Chinese immigrants in Canada within both their current and their past residencies (Canada and China, respectively). Design/methodology/approach: Conceptual guidelines for this study embodied the gift-giving conceptual framework of Sherry (1983) and Chinese cultural values on gift giving (Yau et al., 1999). A qualitative research study was implemented. Specifically, in-depth interviews with Chinese immigrant women mainly from the Greater Toronto Area (GTA) in Ontario, Canada, offered empirical evidence relating to the gestation stage of gift giving. Findings: The findings indicate the complexity of acculturation in gift-giving practices. In terms of gift-giving occasions, Chinese immigrants in Canada, for the most part, adopted the Canadian gift-giving occasions. However, the important role of ethnicity in decision-making is found through their strong sense of differentiation between Chinese and Canadian gift receivers. The results also indicate some Chinese cultural values such as relationship, reciprocity and group orientation as being still important in shaping gift-giving practices, even after immigration to a new country quite distant from the homeland. One cautionary note is that some cultural values such as relationship can be common to both Chinese and Canadian cultural groups. Research limitations/implications: This research was conducted mainly in the GTA in Ontario, Canada. Future studies could address other large Canadian cities with significant bicultural Chinese populations such as Vancouver in British Columbia and Motreal in Quebec. Practical implications: This research extends the knowledge of bicultural consumers by examining the evolving gift-giving practices of Chinese immigrants living in Canada. A good understanding of the cultural values important to bicultural consumers will help marketers to efficiently and effectively allocate their marketing resources in attracting these niche consumers. Social implications: This study has contributed to the broader field of marketing research. Specifically, the current study offers the importance of understanding values transference of bicultural consumers and their behaviours in integrating into the mainstream gift-giving cultural context. Originality/value: This study has contributed by offering evidence of how a minority consumer group formed complex acculturation realities within a gift-giving consumption context. This contribution can be counted as a step towards theoretical advancement in the field of acculturation and of understanding bicultural consumers.